Associations between Burkitt Lymphoma among children in Malawi and infection with HIV, EBV and malaria: results from a case-control study - Mutalima, N; Molyneux, E; Jaffe, H; Kamiza, S; Borgstein, E; Mkandawire, N; Liomba, G; Batumba, M; Lagos, D; Gratrix, F; Boshoff, C; Casabonne, D; et al. (Public Library of Science, 2008)
Background: Burkitt lymphoma, a childhood cancer common in parts of sub-Saharan Africa, has been associated with Epstein Barr Virus (EBV) and malaria, but its association with human immunodeficiency virus (HIV) is not clear. Methodology/principal findings: We conducted a case-control study of Burkitt lymphoma among children (aged ≤15 years) admitted to the pediatric oncology unit in Blantyre, Malawi between July 2005 and July 2006. Cases were 148 children diagnosed with Burkitt lymphoma and controls were 104 children admitted with non-malignant conditions or cancers other than hematological malignancies and Kaposi sarcoma. Interviews were conducted and serological samples tested for antibodies against HIV, EBV and malaria. Odds ratios for Burkitt lymphoma were estimated using unconditional logistic regression adjusting for sex, age, and residential district. Cases had a mean age of 7.1 years and 60% were male. Cases were more likely than controls to be HIV positive (Odds ratio (OR)) = 12.4, 95% Confidence Interval (CI) 1.3 to 116.2, p = 0.03). ORs for Burkitt lymphoma increased with increasing antibody titers against EBV (p = 0.001) and malaria (p = 0.01). Among HIV negative participants, cases were thirteen times more likely than controls to have raised levels of both EBV and malaria antibodies (OR = 13.2; 95% CI 3.8 to 46.6; p = 0.001). Reported use of mosquito nets was associated with a lower risk of Burkitt lymphoma (OR = 0.2, 95% CI, 0.03 to 0.9, p = 0.04). Conclusions: Our findings support prior evidence that EBV and malaria act jointly in the pathogenesis of Burkitt lymphoma, suggesting that malaria prevention may decrease the risk of Burkitt lymphoma. HIV may also play a role in the etiology of this childhood tumor.